Determinants of Environmental Responsibility Disclosure on Mandatory and Voluntary Reporting of Portuguese Listed Firms - Barbosa, F.; Monteiro, A. P.; Pereira, C. (Journal of Environmental Accounting and Management, 2026)
In this study we analyse two Environmental Disclosure Indices (EDI), one obtained from the mandatory reporting (annual report) and the other from the voluntary reporting (sustainability report). More specifically, we construct these indices and compare their evolution. In addition, we examine if they are affected by industry, environmental certification, firm’s operating performance and corporate governance attributes, namely the number and independence of board members. The legitamicy, signalling and voluntary disclosure theories are used to underpin the theoretical relationship between company’s characteristics, corporate governance and environmental disclosure. Based on portuguese listed companies from 2015 to 2017, the results show an increase of 14.6% in the EDI obtained from the annual reports and 25.8% in EDI obtained from the sustainability reporting. In addition, the industry, environmental certification, lucratively, number of members of the board of directors and the ratio of independent members tend to affect the annual report EDI. Regarding the sustainability reporting EDI, the results are identical except for industry and number of board members. While this study brings some insights to such topical issue in Accounting, there is a scarcity of studies for Portuguese firms.